Outcomes of Popliteal Artery Injury; Level 1 Trauma Center Experience from Pakistan - Ansari, Muhammad Kamran; Saleh, Waryam; Tariq, Muhammad Fahad; Hashim, Rubina; Rajper, Najam Uddin; Shah, Syed Zain Ali; Siddiqui, Mishal Shan; Iqbal, Nimrah; Khan, Gulrukh (Indus Journal of Bioscience Research, 2024)
Background: Traumatic vascular injuries, especially popliteal artery injuries, carry a high risk for limb loss which poses a major healthcare problem for patient management in the developing world. Aims:  This study is aimed to investigate the outcomes after traumatic popliteal artery injuries. Our primary objective was to evaluate limb salvage. Secondary objectives included evaluating postoperative functional outcomes at 3 and 6 months. Methods: A retrospective study was conducted at the Department of Vascular & Endovascular Surgery SMBBIT, Karachi from January, 2020 to December, 2022 after ethical review. All patients with a proven popliteal artery were included and data was collected regarding the patients’ demographics, mode of injury, time since injury, coexisting injuries, and peri-operative complications. Results: We identified 103 cases of Popliteal artery injury, including 96% (n=99) males, with a mean age of 30 +/- 12.75 years. The commonest mechanism of injury was firearm assault totaling 59.2% (n=61). The median (IQR) time since presentation was 10 hours. 31.1% (n=32) cases presented within 6 hours of injury. RGSV interposition graft repair was undertaken in 70.9% (n=73) cases while the rest underwent primary amputation (25.2%, n=26) or Popliteal artery ligation (3.9%, n=4). The mean length of stay was 9.0 days (Median 7.0). We recorded a single post-operative mortality (0.9%). At 3- months follow up, 3 patients had undergone a secondary amputation. 18 cases were complicated by wound infections needing debridement. At 6 months, 68.1% were fully ambulating independently fully whereas 23.4% of the patients were ambulating with difficulty. Limb salvage rates were comparable for patients presenting initially to our hospital and referred cases. Conclusions: In conclusion, popliteal artery injuries remain a significant challenge with difficult limb salvage. Early diagnosis, prompt intervention, and meticulous wound care are crucial for optimizing.